Energy and associated greenhouse gas emissions from household appliances in Malaysia - Saidur, Rahman; Masjuki, Haji Hassan; Jamaluddin, M.Y.; Ahmed, S. (Energy Policy, 2007)
Today, electricity is an indispensable key for civilization and development. The trend of electricity consumption is rather escalating. Electricity generation principally depends upon fossil fuels. In one hand, the stocks of these fuels have been confirmed to be critically limited. On the other hanct, in process of electricity generation by means of these fuels, a number of poisonous by-products adversely affect the conservation of natural eco-system. Further, electricity driven appliances use emanate anti-environmental gases that also affect human health and climate. Therefore, estimation of energy consumption for operating household appliances, savings of energy under policy intervention, and emission of poisonous gases in a fast developing country deserve academic attention. This paper focuses on estimation of energy consumption, energy savings, reduction of emissions of greenhouse gases for use of household appliances in Malaysia between 1999 and 2015. In the upstream side of electricity generation, the study estimates the amount of greenhouse gases (GHGs) resulting from burning of fossil fuels. In downstream side, it considers the energy savings and reduction of CHGs. The results show that significant amount of energy can be saved and thus huge volume of toxic emissions can be controlled. The findings can be useful to policy makers as well as household appliances users.